HERG Protein Plays a Role in Moxifloxacin-Induced Hypoglycemia. (16th November 2015) - Qiu, Hai-Yan; Yuan, Sha-Sha; Yang, Fang-Yuan; Shi, Ting-Ting; Yang, Jin-Kui
Abstract : The purpose of this study was to investigate the effect of moxifloxacin on HERG channel protein and glucose metabolism. HERG expression was investigated using immunohistochemistry. The whole-cell patch clamp method was used to examine the effect of moxifloxacin on HERG channel currents. A glucose tolerance test was used to analyze the effects of moxifloxacin on blood glucose and insulin concentrations in mice. Results show that HERG protein was expressed in human pancreatic β -cells. Moxifloxacin inhibited HERG time-dependent and tail currents in HEK293 cells in a concentration-dependent manner. The IC50 of moxifloxacin inhibition was 36.65  μ mol/L. Moxifloxacin (200 mg/kg) reduced blood glucose levels and increased insulin secretion in wild-type mice at 60 min after the start of the glucose tolerance test. In contrast, moxifloxacin did not significantly alter blood glucose and insulin levels in HERG knockout mice. Serum glucose levels increased and insulin concentrations decreased in HERG knockout mice when compared to wild-type mice. The moxifloxacin-induced decrease in blood glucose and increase in insulin secretion occurred via the HERG protein; thus, HERG protein plays a role in insulin secretion.